2016
DOI: 10.1186/s40814-016-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Optimal Personalised Care After Treatment for Gynaecological cancer (TOPCAT-G): a study protocol for a randomised feasibility trial

Abstract: BackgroundGynaecological cancers are diagnosed in over 1000 women in Wales every year. We estimate that this is costing the National Health Service (NHS) in excess of £1 million per annum for routine follow-up appointments alone. Follow-up care is not evidence-based, and there are no definitive guidelines from The National Institute for Health and Care Excellence (NICE) for the type of follow-up that should be delivered. Standard care is to provide a regular medical review of the patient in a hospital-based ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A full description of the trial design is detailed within the published protocol article. 22 Inclusion criteria for participation in the study were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the trial design is detailed within the published protocol article. 22 Inclusion criteria for participation in the study were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The psychological problems can affect treatment compliance and can increase mortality in patients with cancer . Therefore, identifying the risks and patterns of mental disorders and providing adequate clinical support could improve the prognosis in these patients . In the Gynecologic Oncology group (GOG 152) study, it was found that the baseline quality of life was significantly associated with overall survival .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Therefore, identifying the risks and patterns of mental disorders and providing adequate clinical support could improve the prognosis in these patients. 11 In the Gynecologic Oncology group (GOG 152) study, it was found that the baseline quality of life was significantly associated with overall survival. 12 Women with ovarian cancer also experienced higher levels of psychosocial distress compared with women with other female cancers.…”
Section: Introductionmentioning
confidence: 99%